(untitled) (Agricultural Engineering, 2023)
In recent years, the increasing popularity of healthy eating brought about a significant increase in the consumption of fruit and vegetables in the form of juices, purees and cocktails. In the process of their production, the byproduct is pomace, which is treated by the food processing industry as waste. Assuming that pomace accounts for only 20% of the raw material used, annually up to 630 000 tonnes of pomace are obtained globally. However, numerous studies have demonstrated that fruit pomace is a valuable source of many nutritious substances. The objective of the study was to develop a compression-based production technology of apple pomace-based bars, and to assess their quality. Based on the analysis of the structure of produced bars, it can be concluded that their hardness and resistance to cutting does not differ significantly from that of commercial bars made with alternative technology and from different ingredients.